2016
DOI: 10.3856/vol44-issue4-fulltext-17
|View full text |Cite
|
Sign up to set email alerts
|

Interacciones parasito hospedero en peces del intermareal rocoso de la zona centro y centro sur de Chile: comparacion de la diversidad, conectancia y densidad de vinculos

Abstract: RESUMEN.A pesar que la interacción entre parásitos y hospederos es constante, y obligatoria para los parásitos, las variaciones espaciales de estas relaciones son poco conocidas. En este estudio se cuantifica y compara las interacciones parásito-hospedero en peces de pozas intermareales de la zona centro (33°S) y centrosur (36°S) de Chile. Se recolectó un total de 2.081 peces desde 56 pozas intermareales. Se comparó la biomasa y abundancia de peces entre las pozas de las dos zonas: centro (ZC) y centro-sur (ZC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…When possible, parasites were identified at the lowest taxonomic level, considering bibliographic references indicated in Soto et al (2016) and adding others, such as Petrochenco (1971), Zdzitowiecki (1997), Amin et al (2011), and Laskowski & Zdzitowiecki (2017). Abundance and prevalence (sensu Bush et al 1997) were calculated for each species of parasite in each host sample.…”
Section: Parasitological Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…When possible, parasites were identified at the lowest taxonomic level, considering bibliographic references indicated in Soto et al (2016) and adding others, such as Petrochenco (1971), Zdzitowiecki (1997), Amin et al (2011), and Laskowski & Zdzitowiecki (2017). Abundance and prevalence (sensu Bush et al 1997) were calculated for each species of parasite in each host sample.…”
Section: Parasitological Analysismentioning
confidence: 99%
“…Moreover, a temporal fish that spend a short time in the intertidal zone, as Notothenia sp., has low chance to become infected with parasites in that habitat. Consequently, a few generalist parasites could be acquired in the intertidal, such as the copepod Holobomolochus chilensis which has been recorded on several fish from the central coast of Chile (e.g., Muñoz & Olmos 2007, Muñoz & Delorme 2011, Muñoz & Castro 2012, and the digenean Lecithaster macrocotyle that is a frequent parasite in several intertidal fish of central Chile (Soto et al 2016), but it has also been found in different notothen species (Zdzitowiecki 1997), therefore, it is difficult to know if this digenean was acquired in the intertidal zone of central Chile.…”
Section: Fishmentioning
confidence: 99%
See 1 more Smart Citation